Cellular effects of splenectomy on liver regeneration after 70% resection - Andrey Elchaninov; Andrey Elchaninov; Polina Vishnyakova; Polina Vishnyakova; Elena Gantsova; Elena Gantsova; Miroslava Chirkova; Victoria Karyagina; Larkin Anatoliy; Evgeniya Kananykhina; Maria Kuznetsova; Ibrahim Atabekov; et al. (Frontiers in Cell and Developmental Biology)
IntroductionMammalian liver regeneration is a complex process, the regulation of which involves many mechanisms. The immune system has a pronounced influence on the course of reparative processes in mammals. The hepatic portal vein system provides a direct anatomical connection between the liver and the spleen ― the largest lymphoid organ in mammals. Accordingly, the spleen may have a direct effect on liver regeneration as a source of biologically active substances and migrating leukocytes. Specific mechanisms of such influence remain understudied. This study aimed to assess the effect of splenectomy on liver regeneration after 70% resection in mouse model.MethodsMurine model of liver regeneration after 70% resection was reproduced in C57BL/6 male mice, some of them splenectomized 7 days before the liver resection. Proliferation marker Ki67 in the liver was assessed by immunohistochemistry and the protein content for cyclin D1, cyclin A2 and p53 in the liver was assessed by Western blotting. Using TUNEL assay, an increase in the number of apoptotic cells was detected. The highest number of TUNEL+ cells was detected 1 day after liver resection, while the number of apoptotic cells in animals with prior splenectomy was significantly lower compared to animals with preserved spleen. The dynamics of Ly6C+ monocytes and Ly6G+ leukocytes were studied by flow cytometry. Macrophages were isolated from the regenerating liver using magnetic sorting for F4/80 and their gene expression profiles were analyzed using Clariom™ S Assay, mouse. Peripheral blood and splenic monocytes were isolated by magnetic sorting for CD115 and analyzed by Illumina HiSeq 2500 platform RNA sequencing. Migration of peripheral blood and splenic leukocytes to the regenerating liver was studied using allogeneic transplantation of cells derived from B10-GFP mice.Results and discussionAnimals splenectomized prior to the liver resection showed higher rates of cell proliferation along with higher content of р53 protein in the remnant organ. Splenectomy also correlated with decreased rates of Ly6C+ monocyte and Ly6G+ leukocyte migration. Macrophages in the regenerating liver were transcriptomically enriched for signaling pathways associated with monocyte migration, cell adhesion and cell death. As shown by the GFP+ leukocyte transplantation experiment, the leukocytes migrating to the regenerating liver are mainly of splenic origin. According to high-throughput sequencing data, these cells express high levels of cell adhesion molecules. The spleen has a significant effect on liver regeneration through secretion of biologically active substances and migrating leukocytes. Pre-splenectomy leads to a more pronounced liver damage response after 70% resection, as indicated by higher rates of cell proliferation, higher p53 protein content and cell death-associated signaling pathway activation.